2017
DOI: 10.1002/em.22117
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage in kidney transplant patients. Role of organ origin

Abstract: Chronic kidney disease (CKD) patients are characterized by elevated levels of genomic damage. This damage increases when kidney function decreases being maximum in hemodialysis patients. As kidney transplantation improves renal function, and it is related with better survival, the aim of our study was to evaluate potential changes in DNA damage levels after kidney transplantation, and comparing living donor recipients with cadaveric donor recipients. The alkaline comet assay was used to determine DNA breaks an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…After three weeks of immunosuppressive therapy with cyclosporin A, CS and 2.0 g/day of MMF, the micronuclei frequency significantly rose compared with pre‐transplant values. In contrast to these findings, a prospective cohort study by Corredor et al (2017) 53 investigated 50 patients with CKD who underwent renal transplantation. Immunosuppressive maintenance therapy with TAC, MMF and CS caused no significant increase in basal DNA damage or micronuclei formation in peripheral blood cells.…”
Section: Resultsmentioning
confidence: 99%
“…After three weeks of immunosuppressive therapy with cyclosporin A, CS and 2.0 g/day of MMF, the micronuclei frequency significantly rose compared with pre‐transplant values. In contrast to these findings, a prospective cohort study by Corredor et al (2017) 53 investigated 50 patients with CKD who underwent renal transplantation. Immunosuppressive maintenance therapy with TAC, MMF and CS caused no significant increase in basal DNA damage or micronuclei formation in peripheral blood cells.…”
Section: Resultsmentioning
confidence: 99%
“…Kidney transplantation improves kidney function and is correlated with better survival; for example, the 5‐year transplant patient survival rate in Taiwan was 89% . Corredor et al reported that kidney transplant recipients had increased their genomic damage levels at 6 and 12 months after kidney transplantation, particularly in cadaveric donor transplants, compared with those observed before transplantation . In Taiwan, 75.4% of kidney transplant recipients received cadaveric transplants .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, variations in kidney uric acid transporter genes ( SLC2A9 , ABCG2 , SLC22A11 , SLC22A12 , SLC17A1 and the auxiliary molecule PDZK1 ) can be held accountable for most hyperuricemia and gout . DNA damage in kidney transplant patients has been observed . Kuo et al reported that the relative contributions of heritability, common environmental factors, and specific environmental factors to phenotypic variance of gout were 35.1%, 28.1%, and 36.8% in men and 17.0%, 18.5%, and 64.5% in women, respectively, in the Taiwan population …”
Section: Introductionmentioning
confidence: 99%